2012
DOI: 10.1038/jid.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 Inhibitor Nutlin-3a Induces Apoptosis and Senescence in Cutaneous T-Cell Lymphoma: Role of p53

Abstract: P53 is rarely mutated in cutaneous T-cell lymphoma (CTCL) and is therefore a promising target for innovative therapeutic approaches. Nutlin-3a is an inhibitor of MDM2 (human homolog of murine double minute 2), which disrupts its interaction with p53, leading to the stabilization and activation of p53. To investigate the potential therapeutic use of nutlin-3a in CTCL, we screened CTCL lines Hut-78, SeAx, MyLa2000, Mac1, and Mac2a by measuring p53 levels after nutlin-3a treatment. In MyLa2000, Mac1, and Mac2a, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 61 publications
2
35
1
3
Order By: Relevance
“…However, previous studies and our own revealed an absence of p53 in resting Mac-1 cells, 28 and it was not affected by SATB1 suppression ( Figure 3B). Given the high potency of SATB1 as a transcription factor, we postulate that SATB1 may directly regulate CDKN1A transcription in PCALCL cells.…”
Section: Satb1 Regulates P21 Expression By Directly Inhibiting Cdkn1amentioning
confidence: 67%
“…However, previous studies and our own revealed an absence of p53 in resting Mac-1 cells, 28 and it was not affected by SATB1 suppression ( Figure 3B). Given the high potency of SATB1 as a transcription factor, we postulate that SATB1 may directly regulate CDKN1A transcription in PCALCL cells.…”
Section: Satb1 Regulates P21 Expression By Directly Inhibiting Cdkn1amentioning
confidence: 67%
“…Also, 30 patients had MF stage IIB or higher, and tissue for p53 analysis was available in 19 cases (Table 1). Control materials included CTCL cell lines SeAx, MyLa200, and MF1885, together with biopsies from solid tumors with known p53 mutations (19). …”
Section: Methodsmentioning
confidence: 99%
“…In the negative case (case #6), the immunohistochemical negativity may be explained by the fact that the R196Stop mutation likely prevents p53 stabilization, as reported in the HuT-78 T-lymphoma cell line harboring the same homozygous nonsense TP53 R196Stop mutation [14].…”
Section: Mutation In Matched Hg-ien and Egc Lesionsmentioning
confidence: 99%